A self-decoupled three-axis force sensor for measuring the wheel force. (February 2014) - Lin, Guoyu; Pang, Han; Zhang, Weigong; Wang, Dong; Feng, Lihang
The wheel force transducer is an important device in the automotive testing field which can measure the force or torque applied to the wheel. Because existing wheel force transducers are almost commercial products, they are too expensive and technical information about them has not been made public; this slows down the development of the wheel force transducer to a certain extent. Accordingly a three-axis wheel force transducer is presented in this paper which is self-decoupled without calculating the decoupling matrix in theory. Its elastic body has a spoke structure with eight elastic beams, which means that it is easy to fabricate. This paper first introduces the overall elastic body structure of the proposed wheel force transducer. Then the strain gauge arrangement, the principle of strain measurement, the connection modes of the bridge circuits and the rotation decoupling principle for Fx and Fz are analysed, and the self-decoupled characteristics are depicted in detail. Finally, to verify the validity of the designed wheel force transducer, three kinds of experiment are carried out. In the static experiments the static performance and the self-decoupled characteristics of the wheel force transducer are verified; in the dynamic tests, a vehicle dynamics test system is adopted to verify the accuracy of the wheel force transducer in the dynamic environment; in road tests, the sensor is installed in the vehicle to verify whether the output of the proposed wheel force transducer can reflect the variation in the force applied to the wheel in practical applications. The results shows the following: first, the maximum non-linearity error, the maximum hysteresis error and the maximum repeatability error of the proposed wheel force transducer are 0.9% of the full scale, 1.1% of the full scale and 0.5% of the full scale respectively; second, the static coupling rate is about 0.08%, which means that the designed wheel force transducer is self-decoupled in theory; third, the proposed wheel force transducer can measure Fx, Fz and My effectively in real applications.